Injectable conductive nanocomposite hydrogels for cardiac tissue engineering: Focusing on carbon and metal-based nanostructures. (5th July 2022) - Pournemati, Behnam; Tabesh, Hadi; Jenabi, Alireza; Mehdinavaz Aghdam, Rouhollah; Hossein Rezayan, Ali; Poorkhalil, Ali; Ahmadi Tafti, Seyed Hossein; Mottaghy, Khosrow
Graphical abstract: Abstract: Cardiovascular diseases are the leading cause of death today and a significant public health problem. Currently, there is no proper treatment for major cardiovascular diseases such as myocardial infarction (MI) as the heart has a very limited innate capacity for regeneration. Although available therapeutical procedures, e.g. pharmacological interventions, coronary artery bypass graft surgery, and ventricular assistant devices, have significantly improved patients' quality of lives and prolonged their longevities, these ameliorating therapies do not regenerate the injured cardiac tissue. Over the last decade, many studies have been devoted to develop various types of scaffolds for regeneration cardiac tissue especially post-myocardial infarction heart failure. Utilizing injectable conductive hydrogels as a minimally invasive method showed acceptable physicochemical and mechanical properties in vivo; and thus, it turns to a promising approach in field of cardiac tissue engineering (CTE). This review focuses on exploring different electroconductive nanoparticles (i.e. metal- and carbon-based) integrated with natural and synthetic injectable hydrogels. Moreover, the physical effect of these nanostructures in terms of conductivity enhancement and mechanical moduli improvement on hydrogels has been compared and evaluated. Eventually, optimized future injectable conductive hydrogel intended to be used for CTE is discussed.